Pengembangan Modul Manajemen Diri untuk Meningkatkan Keterampilan Manajemen Waktu Siswa SMA - Wahyu Aulia Rahman; Agus Tri Susilo; Adi Dewantoro (Universitas Sebelas Maret, 2022)
Abstract: This study aims to develop a time management module to improve the time management skills of high school students. The development method in this study uses the ADDIE Model, which consists of five stages: analysis, design, development, implementation, and evaluation. This research is limited to the development stage, which consists of the material development stage, module development, and the assessment stage by counseling experts. The developed module received an assessment of the high criteria by two guidance and counseling experts. The results of this assessment indicate that the developed product meets the rules of theoretical validity and is ready to be assessed for its practicality and effectiveness. Further research can be carried out by refining the modules developed in this study by proceeding to the implementation and evaluation stages.